Graduate teaching assistants at the Institute of Chemistry-UNESP, campus Araraquara: features of this docent practice model for graduate students and its implications on the academic environment - Gabriel Garcia (Universidade Estadual Paulista Júlio de Mesquita Filho, 2015)
The teaching practice can represent prominent role on graduate student's formation, but also cause a number of profound implications on the academic environment as a whole, depending on the specific applying model. This study objective was to evaluate the characteristics and academic impacts of the graduate students teaching program applied at the Institute of Chemistry - UNESP, Araraquara. As results, severe deficiencies of institutional mechanisms to mitigate impairment of research and teaching activities were observed, therefore it's recommended that the maintenance of this program adopts improving managerial initiatives to implement and assure application of attenuation mechanisms of academic implications.